Public Perception of Strategic Communication and Management Practices in Nigeria’s Telecommunication Industry - Gbamwuan Ngumimi Winnie; Anthony I. Igyuve; Irma Suryani Siregar (PT Agung Media Publisher, 2025)
Strategic communication and management practices play a critical role in shaping public perception, trust, and organizational sustainability, particularly in highly competitive service industries. In Nigeria’s liberalized telecommunication sector, subscribers increasingly evaluate firms not only based on service performance but also on communication strategies and socio-cultural engagement. This study adopted a mixed-methods research design combining a survey of 169 telecommunication subscribers and 30 in-depth interviews conducted in Abuja, Nigeria. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis to capture interpretive insights into public perception. The findings indicate high public awareness of strategic communication practices, with 89% of respondents recognizing deliberate management strategies. Customer service satisfaction was reported by 62% of subscribers, while 86% agreed that CSR and socio-cultural initiatives positively influence perception. Additionally, 86% of respondents indicated that satisfaction motivates them to promote telecommunication services through interpersonal communication. The results demonstrate that subscribers actively interpret strategic communication, customer service encounters, and CSR initiatives as indicators of organizational credibility and commitment. Strategic communication, service quality, and CSR operate as interconnected management practices that shape trust, reputation, and advocacy behavior within Nigeria’s telecommunication industry.